PID Implementation for Depth Control and Navigation of Underwater Robots: Implementasi PID pada Pengendali Kedalaman dan Navigasi Robot Bawah Air - Hermansyah, Azriel; Taufiqurrohman, Muh.; Rifandi, Safriudin (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2025)
As a maritime nation with vast waters, Indonesia faces challenges in activities such as scientific observation, military operations, and underwater exploration. In this context, the development of underwater robots becomes crucial; however, depth control and navigation remain significant issues. Therefore, this research aims to address these limitations by implementing the PID method for depth control and stability of the underwater robot. By utilizing pressure sensors, gyroscope sensors, and PID control, the underwater robot is able to maintain stable depth at the specified levels and execute maneuvers according to the given angles.